ACUMULĂRI ŞI ZĂCĂMINTE DE METALE RARE PRIVITE PRIN PRISMA TECTONICII GLOBALE (PANGEEA, 2025)
The accumulation and deposits of rare metals on global tectonics perspective. After the formulation of “the global tectonics theory”, doubtless all geological processes are survey by the behavior of the tectonics plates. This study is a tentative to demonstrate, in the first time, that the morphology and the paragenesis of rares and radioactives metals deposits is interacted with the position of this deposits in the tectonics plates and, in the second time, a posible taxonomy of the rares and radioactives metals deposits by this canon.
Keywords: rare metals; global tectonics; tectonic plates; metallogenic processes